ISLAMIC VALUES ENCOUNTERED IN HUMAN LANGUAGE PRODUCTION AND COMPREHENSION AS A MENTAL PROCESS - Nurlaila Nurlaila (Universitas Islam Negeri (UIN) Mataram, 2018)
This study concerned mainly on the islamic values encountered in human language production and comprehension as a mental process. The production of language of human being positioned in Broca’s area and comprehension of language is located in Wernike’s area which are located in human left brain. The process of language in human brain is very abstract; it could not be directly seen by naked eyes. It was done by activating some features of the brain such as Broca’s area, Wernike’s area, angular gyrus, motor cortex, etc. Based on psycholinguistics theory, ability to speak or produce meaningful sounds were innate in human. Its meant that human were genetically predisposed to learn and use language. The phenomenon were closely related to islamics values that those facts specifically and delibrately created by God; the Almighty Allah with certain purposes and that regularity was shown in the nature of thing in the earth. This research aims at investigating the islamic values encountered in human language production and comprehension. This is a descriptive qualitative reasearch that the researcher herself functioned as the key instrument. It was found out that there were several kinds of islamic values found in human language production and comprehension namely social, moral, economical, and religious values. Key Words: Islamic Value, Language Production and Comprehension, Mental Process